First Impressions: How Leader Changes Affect Bilateral Aid - Tobias Rommel; Paul Schaudt (Center for Economic Studies and ifo Institute (CESifo), 2016)
We present a new mechanism to explain politically induced changes in bilateral aid. We argue that shifts in the foreign policy alignment between a donor and a recipient country arising from leadership changes induce reallocation of development aid. Utilizing data from the G7 and 133 developing countries between 1975 and 2012, we show that incoming leaders in recipient countries that politically converge towards their donors receive more aid commitments, compared to those that diverge. Additionally taking donor leader change into account, we find that incumbent recipient leaders have an opportunity to get even more aid when political change in donor countries moves them closer to the donor's foreign policy position. Thus, leadership turnover in recipient and donor countries constitutes a potential breaking point in foreign relations. Otherwise inconsequential deviations in voting alignment become highly consequential for aid provision.
Keywords: D72; F35; F53; O19; 330; dyadic leader change; UNGA voting realignment; development aid